Investigating colloquialization in the British parliamentary record in the late 19th and early 20th century. (May 2020) - Hiltunen, Turo; Räikkönen, Jenni; Tyrkkö, Jukka
Abstract: In this paper, we explore how sociocultural changes were reflected in the parliamentary record, a genre that combines elements of spoken, written and written-to-be-spoken discourses. Our main interests are in the processes of linguistic colloquialization and democratization, understood broadly as tendencies towards greater informality and equality in language use. Previous diachronic studies have established that written language has increasingly adopted features associated with spoken language, although genre and register differences are considerable. Our starting point is that as Parliament has become more demographically representative and as prescriptive norms have loosened in society on the whole, the relative frequency of informal features in parliamentary language may have increased. At the same time, profound changes took place in the practices of recording parliamentary proceedings, most importantly the introduction of the official report in 1909. Our data on British parliamentary debates come from the Hansard Corpus (Alexander and Davies, 2015). We investigate the 60-year-period 1870–1930, which includes reports of parliamentary debates and, after 1909, verbatim reports (in total ca. 40 million words). Adopting a pattern-driven approach, we focus on n-gram frequencies. The analysis first identifies major shifts in the language of the reports using unsupervised grouping methods, and then investigates in more detail the frequency trends of individual n-grams associated with spoken language, as well as their function in parliamentary debates. The findings indicate that the introduction of the official report resulted in clear changes in n-gram frequencies, which can be linked to democratization and colloquialization. Highlights: Hansard provides novel data for studying colloquialisation. The genre of parliamentary record is affected by colloquialisation. Introduction of the Official report marks a major stylistic change in the data. Colloquialisation can be tracked with a data-driven approach using n-gram frequencies.